2004
DOI: 10.1080/01902140490463142
|View full text |Cite
|
Sign up to set email alerts
|

INHALATION ADMINISTRATION OF ALL-TRANS-RETINOIC ACID FOR TREATMENT OF ELASTASE-INDUCED PULMONARY EMPHYSEMA IN FISCHER 344 RATS

Abstract: A past study demonstrated that all-trans-retinoic acid (ATRA) treatment by intraperitoneal injection in a rat model of elastase-induced emphysema caused tissue regeneration as evidenced by a decrease in alveolar size and lung volume and an increase in alveolar number. We postulated that treatment with this retinoid by nose-only inhalation exposure would be a more efficient means of targeting damaged lung tissue. Emphysema was induced in male Fischer 344 rats by intratracheal instillation of pancreatic elastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 21 publications
1
32
1
Order By: Relevance
“…However, there are also studies that failed to show benefits of RA in emphysema (45)(46)(47)(48)(49). The reason for the conflicting findings is unclear.…”
Section: Retinoic Acid From Buds To Alveoli: a Role In Lung Repair Anmentioning
confidence: 66%
“…However, there are also studies that failed to show benefits of RA in emphysema (45)(46)(47)(48)(49). The reason for the conflicting findings is unclear.…”
Section: Retinoic Acid From Buds To Alveoli: a Role In Lung Repair Anmentioning
confidence: 66%
“…Some studies in the elastase-or cigarette smoke-induced rat emphysema model reported the reversal of airspace enlargement [6][7][8] which, however, were mainly based on mean linear intercept measurements, a highly controversially discussed parameter [36]. Focussing on elastase-and cigarette smoke-exposure models of emphysema, only one study using design-based stereology convincingly demonstrated the regeneration of lost alveolar septa after ATRA-therapy [7], whereas others did not find an effect of ATRA on emphysema relevant histological parameters in mice, rats or guinea pigs [9][10][11][12][13]. Limited reversal of functional parameters and of an aerosol-derived measure of airspace size was seen in a papain-induced model of emphysema in dogs [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several experimental studies in rats and mice suggested that regeneration of lost alveolar septa can be achieved by ATRA in elastase-or cigarette smoke-induced emphysema [6][7][8]. However, a number of studies failed to demonstrate a beneficial effect of ATRA in other emphysema models [9][10][11][12][13][14], and beneficial effects in human patients have been marginal so far [15][16][17][18]. The reason for these discrepancies is still unclear [19].…”
mentioning
confidence: 99%
“…To date, systemic application of all-trans-retinoic acid is the only therapeutic intervention that has been demonstrated by means of unbiased stereological tools to reverse some of the effects of elastaseinduced emphysema in rats [31]. However, subsequent studies from other laboratories failed to reproduce these findings in rat [105], mouse [69,106,107] and rabbit [108]. No effect of alltrans-retinoic acid was seen in guinea pigs exposed to smoke [70].…”
Section: Models Of Pulmonary Emphysema H Fehrenbachmentioning
confidence: 99%